2006
DOI: 10.1177/0269881106063275
|View full text |Cite
|
Sign up to set email alerts
|

Ecstasy use and self-reported depression, impulsivity, and sensation seeking: a prospective cohort study

Abstract: Although there are indications that ecstasy users have higher levels of depression, impulsivity, and sensation seeking, it is unknown whether these are consequences of ecstasy use or predisposing factors for starting ecstasy use. We prospectively assessed the predictive value of depression, impulsivity, and sensation seeking on future first time ecstasy use. We also assessed whether depression, impulsivity, and sensation seeking had changed after first ecstasy use. Depression, impulsivity, and sensation seekin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
4

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 64 publications
3
38
4
Order By: Relevance
“…Our findings are consistent with two small scale longitudinal studies ([de Win et al, 2006] and [de Win et al, 2007]), where no association was found between common mental health disorders and later ecstasy use. There is a range of reasons why our results might differ from those of others.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our findings are consistent with two small scale longitudinal studies ([de Win et al, 2006] and [de Win et al, 2007]), where no association was found between common mental health disorders and later ecstasy use. There is a range of reasons why our results might differ from those of others.…”
Section: Discussionsupporting
confidence: 92%
“…The few longitudinal studies that have assessed the nature of the relationship between common mental health disorders and ecstasy use have yielded inconsistent results ([de Win et al, 2006], [Huizink et al, 2006] and [Lieb et al, 2002b]). Two small sample size studies found no relationship ([de Win et al, 2006] and [de Win et al, 2007]), whereas two larger scale longitudinal studies found that anxiety and depression preceded ecstasy use disorders in early adulthood ( [Huizink et al, 2006] and [Lieb et al, 2002b]). …”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies reported increased levels of depression (Sumnall and Cole, 2005), impulsivity (Morgan, 1998;Parrott et al, 2000;Tuchtenhagen et al, 2000;Daumann et al, 2001Daumann et al, , 2004bBond et al, 2004;Butler and Montgomery, 2004), and sensation/novelty seeking (Gerra et al, 1998;Tuchtenhagen et al, 2000;Schifano, 2000;Dughiero et al, 2001) in ecstasy users, although it is unclear whether these associations reflect a causal relationship, that is whether ecstasy use causes changes in mood, impulsivity, and sensation seeking or whether depression, impulsivity, and sensation seeking increase the probability of (heavy) ecstasy use (see also De Win et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Huizink et al (2006) found that childhood anxiety and depression scores predicted later Ecstasy use. It should be noted, however, that one study did not find an association between baseline depression scores and future Ecstasy use (de Win et al 2006).…”
mentioning
confidence: 87%